Controlled population‐based comparative study of USA and international adult [55‐74] neurological deaths 1989‐2014. (18th June 2017) - Pritchard, C.; Rosenorn‐Lanng, E.; Silk, A.; Hansen, L.
Abstract : Objectives: A population‐based controlled study to determine whether adult (55‐74 years) neurological disease deaths are continuing to rise and are there significant differences between America and the twenty developed countries 1989‐91 and 2012‐14. Method: Total Neurological Deaths (TND) rates contrasted against control Cancer and Circulatory Disease Deaths (CDD) extrapolated from WHO data. Confidence intervals compare USA and the other countries over the period. The Over‐75's TND and population increases are examined as a context for the 55‐74 outcomes. Results: Male neurological deaths rose >10% in eleven countries, the other countries average rose 20% the USA 43% over the period. Female neurological deaths rose >10% in ten counties, averaging 14%, the USA up 68%. USA male and female neurological deaths increased significantly more than twelve and seventeen countries, respectively. USA over‐75s population increased by 49%, other countries 56%. Other countries TND up 187% the USA rose fourfold. Male and female cancer and CDD fell in every country averaging 26% and 21%, respectively, and 64% and 67% for CDD. Male neurological rates rose significantly more than Cancer and CCD in every country; Female neurological deaths rose significantly more than cancer in 17 countries and every country for CDD. There was no significant correlation between increases in neurological deaths and decreases in control mortalities. Conclusions: There are substantial increases in neurological deaths in most countries, significantly so in America. Rises in the 55‐74 and over‐75's rates are not primarily due to demographic changes and are a matter of concern warranting further investigation.